2010
DOI: 10.1007/s11661-010-0293-4
|View full text |Cite
|
Sign up to set email alerts
|

Solidification of Aluminum-Copper B206 Alloys with Iron and Silicon Additions

Abstract: Solidification of B206 aluminum alloys with additions of iron and silicon was studied to investigate their combined effect on the formation and precipitation of intermetallics, particularly Fe-rich phases. Iron is precipitated mainly by either (CuFe) or (MnFe) phases, or both depending of the iron and silicon content, as well as the cooling rate. It was found that in alloys having up to 0.3wt% Fe, the precipitation of (CuFe) phase can be largely suppressed if the ratio Si/Fe is close to 1 and the cooling rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(19 citation statements)
references
References 8 publications
(8 reference statements)
3
16
0
Order By: Relevance
“…For alloys B2332 and B3134, the (FeCu) phase was also excluded since it was not present in noticeable quantities. This fact was already observed before and discussed in reference [24] . The absence of (FeCu) phase in B2332 and B3134 explains why there is no downward inflexion of the calculated fraction liquid at around 590°C for these two alloys.…”
Section: Impact Of Alloy Composition On Solidification Path and Hot Tsupporting
confidence: 82%
See 1 more Smart Citation
“…For alloys B2332 and B3134, the (FeCu) phase was also excluded since it was not present in noticeable quantities. This fact was already observed before and discussed in reference [24] . The absence of (FeCu) phase in B2332 and B3134 explains why there is no downward inflexion of the calculated fraction liquid at around 590°C for these two alloys.…”
Section: Impact Of Alloy Composition On Solidification Path and Hot Tsupporting
confidence: 82%
“…In a recent study on solidification of 206 type alloys [24] , the authors showed that the precipitation of the (FeCu) phase could be partially or completely suppressed depending of the iron to silicon ratio as well as the cooling rate. Under favorable conditions, precipitation of (MnFe) phase can bypass the precipitation of the (FeCu) phase, capturing then almost all the iron available.…”
Section: Introductionmentioning
confidence: 99%
“…Combined with the morphology and EDS results, it can be found that there are three kinds of phases: dark Chinese script Al 15 (FeMn) 3 (SiCu) 2 (Į-Fe), gray platelet Al 7 Cu 2 (FeMn) (ȕ-Fe) and light Al 2 Cu networks. Besides, the volume fraction of ȕ-Fe is low due to the high addition of Mn, which is in consist with the results of Kamga et al [4] and Tseng et al [10]. in Fig.…”
Section: Resultssupporting
confidence: 90%
“…The platelet ȕ-Fe (Al 7 Cu 2 (FeMn)) and Chinese script Į-Fe (Al 15 (FeMn) 3 (SiCu) 2 ) are often reported in 206 cast alloys at 0.15%Fe and 0.3%Fe [3][4][5]. Recently, Chinese script Al m (FeMn) and platelet Al 3 (FeMn) are experimentally observed in 206 cast alloys at 0.5%Fe [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Aluminum alloys such as A201 and A206, which have a magnesium content below 1%, are renowned for their high strength and toughness. They also possess excellent corrosion resistance, and their precipitation hardening during heat treatment results in the highest tensile strength among all aluminum casting alloys [ 1 , 2 , 3 , 4 , 5 ]. However, these alloys have some disadvantages, including a relatively high tendency to hot tearing and low corrosion resistance [ 6 , 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%